Intrasynovial Injection of Methylprednisolone Acetate in the Treatment of Adhesive Capsulitis of Shoulder: A Retrospective Study (TAJ: Journal of Teachers Association, 2009)
This study was done in the Out Patient Department of Rajshahi Medical College Hospital. Onehundred and sixty two patients of different age group and sex, treated by intrasynovial injectionof methylprednisolone acetate were followed up as out patients and were included in the study.Apart from few side effects almost all patients showed good response in respect to pain andjoint movement with intrasynovial injection. Out of 21 mild diabetic patients, only 3 patientsshowed a high level of blood glucose and out of 17 mild hypertensive patients, only 4 patientsshowed increase in blood pressure. Twelve patients complained of mild face and ankle oedemathat gradually subsided after cessation of the treatment. Almost all the patients in this studygroup were previously treated outside by various types of non-steroidal anti-inflammatorydrugs.doi: 10.3329/taj.v15i2.3911TAJ December 2002; Vol.15(2): 71-73